How to Wash Rice Properly to Keep the Nutrition in Kencat Village, Bancaran, Bangkalan - Alvia Nur Layli; Azzahroh Arum; Teguh Setiawan Wibowo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this activity is to increase health knowledge and instill it in everyday life about how to wash rice properly and correctly. Furthermore, the community pays more attention to how to process good staple foods so that nutrient intake becomes optimal. Furthermore, the community pays more attention to how to process good staple foods so that the community's intake of nutrients is optimal. This activity consists of four stages. First, the team conducted a survey and analysis of regional problems. Second, planning includes the formation of performances and the preparation of activity programs. The third is implementation, and the fourth is assessment. This activity was held from March 14 to August 15, 2023. Respondents participated well in this activity. The respondents' health knowledge and their awareness of caring about the level of nutrients they consume rose.